Quality of Work Life and Organizational Justice: Its Relation to Citizenship Behavior Among Staff Nurses - Fawzia F. Kamel; Howida H. E. Mahfouz; Mervat A. N. Aref (Evidence-Based Nursing Research)
Context: Quality of work-life and organizational justice increasingly identified as progressive indicators of the functioning and sustainability of the organizations. It claimed to be related to citizenship behaviors and positive behaviors of nurses who have an essential role in strengthening morale and betterment and contributes to the survival of an organization. It is an expression of commitment; make the organization stable by reducing turnover, and attracting new nurses. Aim: Assess the quality of work-life and organizational justice and its relation to citizenship behavior among nurses. Methods: A descriptive correlational research design used to carry out this research. The current study conducted in all in-patient units at Benha University Hospital, AlQaluobia Governate, Egypt. A Convenient sample consisted of 310 staff nurses recruited to achieve the aim of this study. Three tools used to collect the data; organizational justice questionnaire, quality of work-life scale, and organizational citizenship behavior questionnaire. Results: The study revealed that more than three quarters (81%) of staff nurses had high perception level regarding the quality of their nursing work-life; nearly three quarters (74.2%) of staff nurses had high perception level regarding organizational justice. In addition to more than half (56.10%) of staff nurses had high perception level regarding organizational citizenship behaviors. Conclusion: A statistically significant positive correlation revealed among quality of nursing work life, organizational justice, and citizenship behaviors. The study recommended that a staff development program need to be done for nurse managers to deal effectively with new ideas and to promote organizational citizenship behavior. Nurse Managers have to pay attention to the nurses' needs for justice/fairness and professional development to tailor strategies to improve quality of work life.